Cellular effects of AP102, a somatostatin analog with balanced affinities for the hSSTR2 and hSSTR5 receptors. (April 2018) - Streuli, Jeremy; Harris, Alan G.; Cottiny, Cecilia; Allagnat, Florent; Daly, Adrian F.; Grouzmann, Eric; Abid, Karim
Abstract: Background: Somatostatin analogs (SSAs) are first-line medical therapy for the treatment of acromegaly and neuroendocrine tumors that express somatostatin receptors (SSTR). Somatostatin suppresses secretion of a large number of hormones through the stimulation of the five SSTR. However, unbalanced inhibition of secretion as observed with the highly potent SSAs pasireotide causes hyperglycaemia mainly by inhibiting insulin secretion. In contrast, AP102 a new SSAs has neutral effect on blood glucose while suppressing GH secretion. Our objective was to establish the cellular effects of AP102 on SSTR2 and SSTR5 that may explain the differences observed between AP102 and other SSAs. Methods: We compared the binding and agonist activity of AP102 with somatostatin-14, octreotide and pasireotide in HEK293 cells transfected with human SSTR2 and SSTR5 receptors. SSAs signal transduction effects (cAMP concentrations) were measured in forskolin-treated cells in the presence of SSAs. Proliferation and apoptotic effects were determined and binding assays were performed using 125 I- somatostatin-14. Results: AP102 has comparable affinity and agonist effect to octreotide at SSTR2 (IC50's of 112 pM and 244 pM, respectively; EC50's of 230 pM and 210 pM, respectively) in contrast to pasireotide that exhibits a 12–27 fold higher IC50 (3110 pM) and about 5-fold higher EC50 (1097 pM). At SSTR5, AP102 has much higher affinity and stimulating effect than octreotide (IC50's of 773 pM and 16, 737 pM, respectively; EC50's of 8526 pM and 26, 800 pM), and an intermediate affinity and agonist effect between octreotide and pasireotide. AP102, octreotide and pasireotide have variable anti-proliferative effects on HEK cells transfected with SSTR2 and SSTR5. Conclusion: AP102 is a new SSA that better reduces signaling at SSTR2 than SSTR5 and prevents cell proliferation at both receptors. The euglycaemic effect of AP102 observed in preclinical studies may be related to this intermediate agonistic potency between pasireotide and octreotide at SSTR2 and SSTR5. Highlights: AP102 is a novel Somatostatin analogs (SSAs) with a distinct affinity compared to octreotide and pasireotide, the most commonly used SSAs in clinic. AP102 led to reductions in proliferation in both SSTR2 (8.1%) and SSTR5 (12.7%) expressing cells lines, comparable with octreotide and pasireotide. The euglycaemic effect of AP102 observed in preclinical studies is related to its intermediate agonistic potency between pasireotide and octreotide.